Association of Blood Pressure with Overweight in Young Adult Student - Barua, Debjane; Noor, Nazia; Begum, Momtaz; Akhter, Shahin; Barua, Shuvramoy; Jafrin, Nilima (Journal of Chittagong Medical College Teachers’ Association, 2021)
Background: Obesity and overweight in young adult is rising & its deleterious health hazard is becoming a major threat now a days. It is one of the major public health problems globally. Overweight may cause metabolic and endocrinological changes. If untreated, hypertension, cardiovascular disease, hyperglycemia, dyslipidemia, atherosclerosis, metabolic syndrome, cancer may occur. Hypertension is more common in obese and overweight people. This study aimed to observe the association of blood pressure with overweight in young adult students. Materials and methods: This case control study was conducted in the Department of Physiology, Chittagong Medical College, Chattogram. Total 120 students, aged between 18-24 years were included in the study. 60 young adult students with a Body Mass Index (BMI) of 25- 29.9kg/m2 were included in case group as overweight subject and 60 students of same age with a BMI of 18.5- 24.9kg/m2 were taken as a control group. General physical examination was done, anthropometric measurements- Height, weight, BMI and pulse, systolic blood pressure and diastolic blood pressure were measured. Pulse Pressure (PP) and mean arterial pressure were calculated. For statistical analysis unpaired student’s ‘t’ test, chisquare test and correlation coefficient were done by using SPSS for windows version-25. Results: Systolic Blood Pressure (SBP) Diastolic Blood Pressure (DBP) and Mean Arterial Pressure (MAP) were significantly high in overweight (Case) students (p<0.001). Frequency of prehypertension was more in overweight group (p<0.001) comparing to normal weight group. Significant positive correlations (p<0.05) were observed among BMI with SBP, DBP and MAP in overweight young adult students. Conclusion: According to present results it was concluded that apparently healthy overweight young adult students were associated with increased blood pressure than normal weight students. JCMCTA 2021 ; 32 (2) : 47-52